Kepatuhan Wajib Pajak Memoderasi Pengaruh Kesadaran, Pemeriksaan, dan Penagihan terhadap Penerimaan Pajak - Dinda Kurnia Ramadhani Batubara; Desi Ika (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine how taxpayer awareness, tax audits, and tax collection affect tax revenue, with taxpayer compliance acting as a moderating variable. Data was collected by distributing questionnaires to respondents who were registered taxpayers at the East Medan Tax Office (KPP), with a sample size of 100 people. The analytical technique used in this study is Moderated Regression Analysis (MRA). The analysis results show that the three independent variables, namely taxpayer awareness, tax audits, and tax collection, have a significant effect on tax revenue, as indicated by their respective significance values of 0.000. However, when tested as a moderating variable, taxpayer compliance was only found to significantly moderate the relation between taxpayer awareness and tax revenue (p-value 0.005). Conversely, taxpayer compliance did not show a significant moderating effect in the relations between tax audits (p-value 0.114) and tax collection (p-value 0.592) on tax revenue.